Lend Me Your Ears: Mass Observing Contemporary Adult Reading Aloud Practices. Issue 4 (2nd October 2018) - Duncan, Sam
ABSTRACT: Reading aloud receives a great deal of attention as something done with children and as a potential teaching tool, but less is known about the oral reading that we, as adults, may do for various purposes across our everyday lives. This article explores one element of a two-year project recording and analysing contemporary adult reading aloud practices. It reports on an analysis of all 160 Mass Observation Project responses, examining the 'atypical typicality' of correspondents' reactions to the topic and their own practices; their analytical acts as researchers classifying practices and investigating artistry; and the stories they tell about how we both express and create relationships with individuals and larger groups through our oral reading practices. Contemporary adult reading aloud practices, as presented, analysed and narrated by the Mass Observers, are ubiquitous, often invisible, hugely varied, and matter to us as individuals and communities.